2022
DOI: 10.1021/acs.joc.2c00756
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced [6π]-Electrocyclic Reaction of Mono-, Di-, and Trisubstituted Triphenylamines in Acetonitrile. A Steady-State Investigation

Abstract: Direct irradiation of mono-, di-, and trisubstituted triphenylamine derivatives in acetonitrile as solvent with light of 254 nm has been systematically investigated, revealing that the exo/endo carbazole derivatives were formed as the main photoproducts from modest to good yields for triphenylamines substituted with electron-donor and neutral substituents. The kinetic profiles of the photoreaction were also recorded, and the consumption rate constants (k) were measured. These kinetic parameters show dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 79 publications
0
16
0
1
Order By: Relevance
“…Furthermore, a remarkable Hammett substituent effect on the rate constants ( k obs ) was observed, and bell-shape behaviors were obtained with solvents of different polarity as it was observed when ρ values were correlated with the E T (30) parameter (Figure ). Therefore, a proposed reaction mechanism for the photoinduced [6π]-electrocyclic reaction of monosubstituted triphenylamines is depicted in Scheme , which is supported by our results obtained under steady-state conditions and those reported previously in the literature. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a remarkable Hammett substituent effect on the rate constants ( k obs ) was observed, and bell-shape behaviors were obtained with solvents of different polarity as it was observed when ρ values were correlated with the E T (30) parameter (Figure ). Therefore, a proposed reaction mechanism for the photoinduced [6π]-electrocyclic reaction of monosubstituted triphenylamines is depicted in Scheme , which is supported by our results obtained under steady-state conditions and those reported previously in the literature. ,, …”
Section: Resultsmentioning
confidence: 99%
“…The substituent effect was also studied on the photoinduced [6π]electrocyclization reaction of a family of mono-, di-, and trisubstituted triphenylamine in acetonitrile under steady-state conditions. 20 This systematic investigation revealed that the exo/endo carbazole derivatives were formed as the main photoproducts in modest to good yields for triphenylamines substituted with electron-donor and neutral substituents. However, the photoreaction of triphenylamines substituted with electron-withdrawing substituents did not proceed, while intramolecular charge transfer complexes were formed due to the nature of the substituents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…80 Bonesi and co-workers developed a catalyst-free photochemical strategy for the synthesis of exo/endo carbazoles from triphenylamines (31a) having electron-donor and neutral substituents (Scheme 31). 81 It was reported that, upon irradiation with 254 nm UV light, mono-, di-and tri-substituted triphenylamines containing electron donor (-Me, -OMe, -NH2), electron neutral (H) and -Cl, were able to deliver the corresponding carbazoles with good yields in acetonitrile. However, the compounds containing electron withdrawing group (-CHO, -COMe, -NO2) failed to afford the carbazole derivatives due to the formation of a charge transfer complexes in the excited state.…”
Section: Miscellaneous Illustration Of C-c Bond Formations Via Cycliz...mentioning
confidence: 99%
“…Photoinduced electrocyclization of substituted triphenylamines. 81 Gentili and co-workers demonstrated a diastereoselective Norrish-Yang cyclization of 2-(hydroxyimino)aldehydes 32a to afford cyclobutanol oximes 32b without giving any traditional fragmentation product upon irradiation of 365 nm UV-LED (Scheme 32). 82 This efficient stratigy offered a libray of cyclobutanol oximes without the use of any photosensitizer in short reaction time.…”
Section: Miscellaneous Illustration Of C-c Bond Formations Via Cycliz...mentioning
confidence: 99%
See 1 more Smart Citation